Konsep dan Perkembangan Masjid: Studi Kasus Masjid Nurul Huda Babat Toman - Ipel Purnama Sari; Indah Nurafwa Sari; Intan Okta Riani; Hudaidah Hudaidah; Tyas Fernanda (Jurnal Ilmu Sosial dan Humaniora, 2026)
As a place of worship for Muslims, mosques play an important role in religious, social, and educational aspects of society. Mosques not only serve as a place to perform congregational prayers, but also as a center for missionary activities, community development, and social interaction within the surrounding community. Historically, mosques have undergone changes in function and building design in line with the progress of the times and the needs of society. These changes illustrate that mosques have adapted to various historical phases. This article was written to discuss the basic foundations of mosques, including their definition, function, history, and development. In addition, this article also focuses on the history and development of the Nurul Huda Babat Toman Mosque. In this study, the method used is qualitative with a historical approach. Data was obtained through interviews with relevant sources and by searching for articles and scientific journals related to the topic being studied. The findings of the study show that the Nurul Huda Babat Toman Mosque is very important for the religious life of the local community. This mosque has also undergone developments over time, both in terms of its functionality and its existence in the community. In conclusion, the discussion of the basic concepts of this mosque provides a clearer understanding of the position and meaning of the Nurul Huda Babat Toman Mosque in the context of the history and life of the community in the area.